Research on the output coordinated strategy of a DPFC considering device fault probability - Chen, Xiaogang; Tang, Aihong; Xiong, Binyu; Zhou, Wei (Frontiers in Energy Research, 2022)
A distributed power flow controller (DPFC) can control the line power flow in a flexible and fast way to meet the requirements of a new power system. However, the output of DPFC sub-units is generally distributed by the even distribution method or proportional distribution method at present. The internal health status and output capacity of the device are not taken into account, which affects the efficiency and service life of the device. In this article, a reliability description method of DPFC based on fault probability is proposed. The coordination strategy of output voltage capability and the number of input sub-units is proposed, and the process of the proposed coordinated strategy for device output is presented. The simulation results show that the proposed coordinated output strategy can address the issue of rapid reliability decline caused by the long-term work of some sub-units and improve the overall reliability of the DPFC.